1999
DOI: 10.1017/s0007114599000112
|View full text |Cite
|
Sign up to set email alerts
|

The ‘Mini Nutritional Assessment’ (MNA) and the ‘Determine Your Nutritional Health’ Checklist (NSI Checklist) as predictors of morbidity and mortality in an elderly Danish population

Abstract: The purpose of the present study was to evaluate the capacity of the'Determine Your Nutritional Health' Checklist (NSI Checklist) and the 'Mini Nutritional Assessment' (MNA) methods to predict nutrition-related health problems. Data were from the Danish part of the 'Survey in Europe of Nutrition in the Elderly, a Concerted Action' (SENECA) baseline survey from 1988, and the follow-up study from 1993. Based on the baseline survey thirty-nine (19 . 3 %) of the subjects were classified at high nutritional risk, 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
73
0
9

Year Published

2002
2002
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(89 citation statements)
references
References 8 publications
7
73
0
9
Order By: Relevance
“…In a Danish population-based study by Beck et al 21 on 202 men and women, 70-75 years old, the unadjusted HR to die was 0.35 (95% CI 0.18-0.66) for the group with a MNA score 423.5 compared with the group with a MNA score p23.5. In a Taiwanese study, Tsai et al 12 followed 2802 men and women aged 465 years for 4 years and the age-adjusted HR for the same group was 2.39 (95% CI 1.99-2.88).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…In a Danish population-based study by Beck et al 21 on 202 men and women, 70-75 years old, the unadjusted HR to die was 0.35 (95% CI 0.18-0.66) for the group with a MNA score 423.5 compared with the group with a MNA score p23.5. In a Taiwanese study, Tsai et al 12 followed 2802 men and women aged 465 years for 4 years and the age-adjusted HR for the same group was 2.39 (95% CI 1.99-2.88).…”
Section: Discussionmentioning
confidence: 95%
“…A study on free-living elderly, MNA and mortality conducted by Beck et al 21 showed that participants with a MNA score 423.5 had a hazard ratio (HR) of 0.35, regarding the risk to die during the 5-year follow-up, compared with participants with a MNA score p23.5.…”
Section: Introductionmentioning
confidence: 99%
“…O idoso (60 ou mais anos) (5) apresenta peculiaridades relacionadas com o processo de envelhecimento, como: a) redução progressiva da altura, de um a dois cm por década; b) ganho progressivo de peso e IMC até em torno de 65 a 70 anos, diminuindo a partir de então; c) alterações da composição corporal, com redistribuição de gordura, que diminui a nível periféri-co e aumenta no interior do abdome, e redução da massa magra (5,13,62). Alguns autores consideram que a desnutrição pode ser difícil de distinguir das alterações resultantes do processo natural do envelhecimento (62,63), porém se não for detectada, pode resultar em agravamento de condições clínicas e aumento da mortalidade (62).…”
Section: Aspectos Peculiares Do Idosounclassified
“…Alguns autores consideram que a desnutrição pode ser difícil de distinguir das alterações resultantes do processo natural do envelhecimento (62,63), porém se não for detectada, pode resultar em agravamento de condições clínicas e aumento da mortalidade (62). A população idosa é particularmente propensa a problemas nutricionais devido a fatores relacionados com as alterações fisiológicas e sociais, ocorrência de doença crônica, uso de várias medicações, problemas na alimentação (comprometendo a mastigação e deglutição), depressão e alterações da mobilidade com dependência funcional (62,64,65).…”
Section: Aspectos Peculiares Do Idosounclassified
“…The k statistic for the MNA total score has been shown to be 0.51 (95% CI 0.28 -0.74; Gazzoti et al, 1997). The MNA has been found to predict length of hospital stay, costs (Pertoldi et al, 1996), and mortality (Beck et al, 1999;Comban et al, 1999). The tool has been used in elderly Swedish people receiving primary health care (Wissing & Unosson, 1999) and those in home nursing care (Saletti et al, 1999).…”
Section: Introductionmentioning
confidence: 99%